Brilliant discourse: pictures and readers in early modern Rome - Lincoln, Evelyn (Yale University Press, 2014)
Pictures and Readers in Early Modern Rome -- Pictures for the Ear of the Heart : The Life and Miracles of St. Benedict -- Camillo Agrippa's Cosmology of Knowledge -- The Care of the Body in Pietro Paolo Magni's Manual for Barber-Surgeons -- Coyrts and Other Theatres : Magino Gabrielli's Dialogues on Silk -- Talking Pictures : The Discourse of Images in Illustrated Dialogues